Comparison of Streptokinase Activity from Streptococcus mutans using Different Substrates - Muhammad Anjum Zia*, Rana Faisal, Rao Zahid Abbas1, Gull-e-Faran, Muhammad Kashif Saleemi2 and Junaid Ali Khan3 (Pakistan Veterinary Journal, 2013)
Streptokinase is a novel bacterial fibrinolytic enzyme that binds and activates plasminogen and is produced by several species of Streptococci. Streptococcus mutans was selected for optimum production of streptokinase using corn steep liquor, molasses, rice polishing and sugarcane bagass in liquid state fermentation. Substrates were applied in different concentrations ranging from 0.1-0.8%. Maximum fibrinolytic activity was observed by 0.3% corn steep liquor, 0.5% molasses and rice polishing and 0.4% by sugarcane bagass. The fibrinolytic activity achieved by fibrin clot lysis method was 5.5, 5.08, 5.16 and 4.75 units using corn steep liquor, molasses, rice polishing and sugarcane bagass, respectively.